Phosphorus in Oil Palm Cultivated in the Oriental Amazon - Viegas, Ismael de Jesus Matos; Farias, Magda do Nascimento; Ferreira, Eric Victor de Oliveira; Barata, Henrique da Silva; Conceição, Heráclito Eugênio Oliveira da; Galvão, Jessivaldo Rodrigues; Silva, Diocléa Almeida Seabra (Journal of Agricultural Studies, 2021)
Amazon soils have a low phosphorus (P) availability and few studies have investigated nutrition of palm oil plantations. This study assessed the effects of P nutrition on oil palm organs according to plant age. The experiment was carried out under field conditions, at the enterprise Agropalma S/A, in the municipality of Tailândia, Pará State, Brazil. The experimental design used was completely randomized with four replications and comprised seven treatments: plants age (2, 3, 4, 5, 6, 7, and 8 years of planting). We evaluated P concentration, accumulation, and exportation in plant components (leaflets, petioles, stipe, rachis, palm heart, arrows, male inflorescences, peduncles, spikelets, and fruits). Palm heart (10.9 g kg-1) and male inflorescence (3.8 g kg-1) showed the highest P concentrations in the vegetative and reproductive organs, respectively. On the other hand, the largest P accumulations were observed in the stipe (159 g plant-1) and fruits (59 g plant-1), increasing from the 3rd year of age of the plants. Bunches exported the largest P amounts (81 g plant-1), especially in older plants. The oil palm immobilizes (24 kg ha-1) and recycles (23 kg ha-1) a large amount of P, more than it exports (12 kg ha-1) P.